2018
DOI: 10.1186/s13287-018-0936-8
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stromal cells inhibit platelet activation and aggregation involving CD73-converted adenosine

Abstract: BackgroundMesenchymal stromal cells (MSCs) are promising cell therapy candidates. Clinical application is considered safe. However, minor side effects have included thromboembolism and instant blood-mediated inflammatory reactions suggesting an effect of MSC infusion on hemostasis. Previous studies focusing on plasmatic coagulation as a secondary hemostasis step detected both procoagulatory and anticoagulatory activities of MSCs. We now focus on primary hemostasis and analyzed whether MSCs can promote or inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…However, minor side effects, including thromboembolism and immediate blood-mediated inflammatory response, do occur suggesting the effect of MSC infusion on hemostasis. 38 Adipose-derived mesenchymal stem cells seem to possess more stable pro-coagulant activity than bone marrow-derived MSCs, which raises potential safety concerns for its systemic administration into patients with clotting diseases. There are donor variants available among different cell populations, and the coagulation conditions can also be determined by the culture conditions used for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, minor side effects, including thromboembolism and immediate blood-mediated inflammatory response, do occur suggesting the effect of MSC infusion on hemostasis. 38 Adipose-derived mesenchymal stem cells seem to possess more stable pro-coagulant activity than bone marrow-derived MSCs, which raises potential safety concerns for its systemic administration into patients with clotting diseases. There are donor variants available among different cell populations, and the coagulation conditions can also be determined by the culture conditions used for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that BMSCs are dependent on their tissue of origin and inhibit platelet activation with the help of formation of adenosine from adenosine monophosphate due to the ecto-5ʹ-nucleotidase activity of CD73. 38 Hence, Na 2 SeO 3 may inhibit the coagulation mediated by BMSCs by affecting the differentiation of BMSCs. Consistent with previous studies, our study showed the inhibitory effect of Na 2 SeO 3 on the BMSC-mediated coagulation process.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the Mannheim Ethics Commission II (vote numbers 2015-520N-MA, 49/05 and 2006-192 N-MA, respectively). BM, CB and ASC were isolated and characterized as previously described [27]. Following isolation, ASC and BM were continuously cultured at a density of 200 cells/cm 2 and CB at 700 cells/cm 2 in DMEM (PAN Biotech; Aidenbach, Germany) supplemented with 10% pooled human allogeneic AB serum from healthy donors (German Red Cross Blood Donor Service Baden-Württemberg-Hessen, Mannheim, Germany), 1% penicillin/streptomycin (100,000 U/mL penicillin and 10 mg/mL streptomycin; PAN Biotech) and 2% L-glutamine (200 mM; PAN Biotech) (=DMEM-AB).…”
Section: Cell Culturementioning
confidence: 99%
“…In contrast, recently, Netsch et al [67] published that MSCs from different origins (bone marrow, adipose and cord blood) express anticoagulant properties, affecting primary hemostasis. They showed that MSCS inhibit the agonist-induced activation and aggregation of platelets in platelet-rich plasma (PRP) and whole blood.…”
Section: Procoagulant Activitymentioning
confidence: 99%